STRUKTUR MODAL, CURRENT RATIO, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN ROA SEBAGAI MODERATING - Herlambang, Albert; Pakpahan, Effendy; Rahmi, Namira Ufrida (RISTANSI: Riset Akuntansi, 2024)
The purpose of this research is to study and analyze the influence of capital structure, current ratio, and company size on company value with return on assets as a moderating variable in food and beverage businesses listed on the Indonesia Stock Exchange from 2019 to 2023. This quantitative research uses documentation method. 39 food and beverage companies listed on the Indonesia Stock Exchange are the subjects of this research. The purposive sampling method was used to select 17 companies for this research. Data analysis was carried out using moderation analysis using the SPSS analysis program. The results show that 1) capital structure has a negative effect on firm value, 2) current ratio has a positive effect on firm value, 3) firm size has a negative effect on firm value, 4) return on assets can moderate the effect of capital structure on firm value, 5) return on assets can moderate the effect of the current ratio on firm value, 6) return on assets can moderate the effect of firm size on firm value.